Biaya Peremajaan Kelapa Sawit Rakyat Dari Berbagai Sumber Dana Di Kecamatan Sungai Bahar Kabupaten Muaro Jambi - Sri Rahayu, Agustini; HD, Ernawati; Rahman, A (JALOW | Journal of Agribusiness and Local Wisdom, 2022)
Muaro Jambi Regency is one of the district's oil palm production centers in Jambi Province. Oil palm production decreases every year due to the presence of old oil palm plantations and one of the efforts to increase oil palm production is oil palm rejuvenation. This study aims to describe the implementation and costs of oil palm rejuvenation from various funding sources in the research area, and to analyze the differences in the costs of oil palm rejuvenation from various funding sources. The method of analysis in this study is descriptive analysis and the analysis of the Z-test Difference Test. The results of this study indicate that there is a difference between the two costs of oil palm rejuvenation, a decision is obtained that significantly: (a) The cost of oil palm rejuvenation from conventional BPDPKS funding sources is higher than Mandiri underplanting techniques. The value of Asymp.sig (2 tailed) is 0.000 < = 5% 0.05 and the value of z-count > z-table (6,339 > 0.999) so that a decision to reject H0 is obtained; (b) The cost of oil palm rejuvenation from conventional technical BPDPKS funding sources is higher than conventional technical BI funding sources. The value of Asymp.sig (2 tailed) is 0.005 < = 5% 0.05 and the value of z-count > z-table (2.785 > 0.997) so that a decision to reject H0 is obtained; (c) The cost of oil palm rejuvenation from conventional technical BPDPKS funding sources is higher than conventional technical technical APBN sources. The value of Asymp.sig (2 tailed) is 0.000 < = 5% 0.05 and the value of z-count > z-table (3.989 > 0.999) so that a decision to reject H0 is obtained.